2019
DOI: 10.12968/bjom.2019.27.5.297
|View full text |Cite
|
Sign up to set email alerts
|

Diet and physical activity in pregnancy: a study exploring women's beliefs and behaviours

Abstract: Background Being obese or gaining excessive weight during pregnancy can increase health risks for mother and baby. Adopting a healthy diet and increasing physical activity reduces these risks and has long-term health benefits for women. Despite this, women do not always maintain a healthy lifestyle during pregnancy. Aim To explore the factors that encouraged and prevented a diverse group of women to maintain a healthy lifestyle during pregnancy. Methods A total of 12 women participated in semi-structured quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
1
4
1
Order By: Relevance
“…In this study, users also perceived the exercises performed by influencers as unachievable for themselves and made comparisons between the capabilities of the influencer and themselves [ 8 , 39 ]. This contrasts somewhat with previous research that suggests the ability of an influencer to perform difficult or advanced exercises while pregnant inspires some users to engage in similar exercises [ 40 ]. Our findings demonstrated positive attitudes of trust in the influencer’s knowledge, with users generally perceiving influencers as having expertise in exercise during pregnancy, and commenting about the inspiration and motivation they drew from the influencer.…”
Section: Discussioncontrasting
confidence: 91%
See 1 more Smart Citation
“…In this study, users also perceived the exercises performed by influencers as unachievable for themselves and made comparisons between the capabilities of the influencer and themselves [ 8 , 39 ]. This contrasts somewhat with previous research that suggests the ability of an influencer to perform difficult or advanced exercises while pregnant inspires some users to engage in similar exercises [ 40 ]. Our findings demonstrated positive attitudes of trust in the influencer’s knowledge, with users generally perceiving influencers as having expertise in exercise during pregnancy, and commenting about the inspiration and motivation they drew from the influencer.…”
Section: Discussioncontrasting
confidence: 91%
“…Access to credible information affects both the attitudes towards exercise during pregnancy and a pregnant woman’s perceived behavioural control, which is the confidence, resources, and ability they have to overcome the barriers they experience [ 48 , 49 ]. Information about the risks, benefits, and prescription of exercise during pregnancy could improve the confidence of pregnant women, contribute to their sense of control to engage in exercise [ 49 ], improve attitudes towards exercise [ 32 ], and overall, encourage women to participate in exercise [ 40 ]. Advice received from healthcare providers about exercise during pregnancy is often conservative, likely owing to a lack of understanding or awareness on the part of the health professional [ 45 , 50 ], and may not include information about the safety and efficacy of resistance-based exercise using weights [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our findings also align with previous studies that found pregnant patients positively perceive provider counseling on PA (Harrison et al, 2019, Heim et al, 2019, Whitaker et al, 2016 and often initiate it (Whitaker et al, 2019); however, provider communication regarding PA and behavior change is often ineffective (Blankenship et al, 2020, Chana, 2019. The Covid-19 pandemic has further decreased the time and energy providers have available for counseling patients, with many providers stretched to burnout (Bradford and Glaser, 2021).…”
Section: Discussionsupporting
confidence: 89%
“… I have spent sometimes £15 on one meal that is going to be really healthy and I could just go buy a pizza for £2. (Chana & Haith-Cooper, 2019 ) …”
Section: Resultsmentioning
confidence: 99%